1990
DOI: 10.1113/jphysiol.1990.sp018094
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the intracellular free calcium concentration in single rat dorsal root ganglion neurones in vitro.

Abstract: SUMMARY1. Simultaneous whole-cell patch-clamp and Fura-2 microfluorimetric recordings of calcium currents (ICa) and the intracellular free Ca2+ concentration ([Ca2+]i) were made from neurones grown in primary culture from the dorsal root ganglion of the rat. Cells held at -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
289
7
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(337 citation statements)
references
References 53 publications
(90 reference statements)
40
289
7
1
Order By: Relevance
“…Exacerbated activation of glutamate receptor-coupled calcium channels and subsequent increase in intracellular calcium concentrations ([Ca 2+ ] i ), followed by sustained disturbances in the [Ca 2+ ] i homeostasis, are established hallmarks of neuronal cell death in acute and chronic neurological diseases (29,30). Interestingly, activation of potassium intermediate/small conductance calciumactivated channel K Ca 2 prevented [Ca 2+ ] i deregulation and reduced neuronal death following glutamate toxicity and cerebral ischemia (31).…”
Section: Resultsmentioning
confidence: 99%
“…Exacerbated activation of glutamate receptor-coupled calcium channels and subsequent increase in intracellular calcium concentrations ([Ca 2+ ] i ), followed by sustained disturbances in the [Ca 2+ ] i homeostasis, are established hallmarks of neuronal cell death in acute and chronic neurological diseases (29,30). Interestingly, activation of potassium intermediate/small conductance calciumactivated channel K Ca 2 prevented [Ca 2+ ] i deregulation and reduced neuronal death following glutamate toxicity and cerebral ischemia (31).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has demonstrated mitochondrial site specificity for CCCP (Thayer and Miller, 1990;Friel and Tsien, 1994;Buttgereit and Brand, 1995;Park et al, 1996). Because the intramitochondrial calcium concentration is usually larger than that in the cytosol, CCCP application causes a transient increase in cytosolic calcium and a decrease in mitochondrial calcium (Biscoe et al, 1989;Simpson and Russell, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…From the classical viewpoint, adequate levels of ATP are essential to maintain the neuronal plasma membrane potential via the sodium-potassium ATPase, which consumes about 40% of the energy (1). In addition, mitochondria are an important intracellular Ca 2þ sequestration system (2,3), and especially synaptic mitochondria are indispensible for neurotransmitter reserve pool mobilization in the presynaptic compartment (4). Due to these important features, mitochondria can modulate neuronal excitability and synaptic transmission (5,6).…”
mentioning
confidence: 99%